2018
DOI: 10.1021/acsomega.7b01634
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Desmethyl Jahanyne and Its Lipo-Tetrapeptide Conjugates Derived from Parent Skeleton as BCL-2-Mediated Apoptosis-Inducing Agents

Abstract: The total synthesis of highly potent and scarcely available marine natural product (−)-jahanyne was attempted resulting in a solution-phase synthesis of pruned versions with comparable activity. A simple and facile synthetic route was employed for the preparation of pruned congeners and would be scalable. The lipophilic tail of the natural product was synthesized from R-(+)-citronellol, utilizing easily available chemicals. All the synthesized compounds were screened for apoptotic activity against a panel of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Cells were trypsinized and harvested in the presence of protease inhibitor. Samples were subjected to heat at incremental temperatures of 42, 46, 50, 54, 58 and 62 °C for 3 min followed by immediate freeze/thaw in liquid nitrogen and at 25 °C as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were trypsinized and harvested in the presence of protease inhibitor. Samples were subjected to heat at incremental temperatures of 42, 46, 50, 54, 58 and 62 °C for 3 min followed by immediate freeze/thaw in liquid nitrogen and at 25 °C as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Marinopyrrole A (Maritoclax) is a natural product derived from marine streptomycetes that appears to specifically bind Mcl-1 and target it for proteosomal degradation [ 47 ]. Some synthetic analogues of the marine natural compound jahanyne, isolated from Lyngbya sp., were shown to induce apoptosis in cancer cells by binding Bcl-2 [ 48 ]. The marine natural compound renieramycin M has been shown to downregulate Mcl-1 and Bcl-2 expression in a p53 dependent manner in cancer cells and sensitize them to undergo anoikis [ 49 ].…”
Section: Caspase Dependent Apoptosismentioning
confidence: 99%
“…The data from the initial MTT assays revealed that jahanyne inhibited the growth of both HL60 cells and HeLa cells with an IC 50 (half-inhibitory concentration) value at the micromolar level and could induce apoptosis in HeLa cells. The bolaamphiphile-mimicking structure of jahanyne and its potent anticancer activity have attracted attention not only from the synthetic community but also from the biological community [19][20][21][22]. Chandrasekhar et al first completed the total synthesis of desmethyl jahanyne [19].…”
Section: Introductionmentioning
confidence: 99%
“…The bolaamphiphile-mimicking structure of jahanyne and its potent anticancer activity have attracted attention not only from the synthetic community but also from the biological community [19][20][21][22]. Chandrasekhar et al first completed the total synthesis of desmethyl jahanyne [19]. Preliminary MTT biological assays of desmethyl jahanyne and synthetic intermediates indicated that the N-methyl group and terminal alkynyl fatty acid motifs were essential for maintaining jahanyne's inhibitory activities against cancer cells.…”
Section: Introductionmentioning
confidence: 99%